Hubungan Kecerdasan Emosional dan Spiritual Santri terhadap Hafalan Al-Qur’an di Pondok Pesantren Tahfizul Qur’an - Huda, Ahmad Raudlatul (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2023)
The background of this research is that the memorization of the Koran by tahfidz students at the tahfidz al-Qur'an Ma'unah Sari Islamic Boarding School has experienced a significant decline. This type of research uses a quantitative approach, using simple linear regression analysis and multiple regression of the SPSS output. The focus of the research includes: (1) How is the Emotional Intelligence of the tahfidz students? (2). How is the Spiritual Intelligence of the tahfidz students? (3). How is the Memorization of the Qur'an of the Tahfidz students? (4). Is there a relationship between the Emotional intelligence of the students towards memorizing al- Qur'an? (5). Is there a relationship between the spiritual intelligence of the santri towards memorizing the Qur'an? (6). Is there a relationship between the emotional and spiritual intelligence of the santri towards the memorization of the al-Qur'an at the Tahfidzul Qur'an Maunah Sari Islamic Boarding School? The results of the study concluded that (1) the emotional intelligence of the tahfidz ma'unah sari students had an average score of 98.68 which was in the good category (2) the spiritual intelligence of the tahfidz ma'unah sari students had an average score of 140.8 included in the good category (3) the memorization of the Koran by the students of tahfidz ma'unah sari had an average score of 106.76 which was included in the good category. (4) the regression coefficient X is 0.793 which states that the addition of 1% emotional intelligence will increase the memorization of the Koran by 0.79 so that the higher the emotional intelligence of the students, the higher the level of memorization of the Koran by students. (5). the regression coefficient X is 0.607 which states that the addition of 1% spiritual intelligence will increase the memorization of the Koran by 0.607 so that the higher the spiritual intelligence of the students, the higher the level of memorization of the Koran by students. (6). The relationship of emotional intelligence and the spirituality of the students towards memorizing the Koran by 42% while the rest (100% -42% = 58%) is influenced by other variables not examined in this study